STRATEGI MANAJEMEN RISIKO PEMANFAATAN TEKNOLOGI PADA LEMBAGA KEUANGAN SYARIAH ERA MILLENNIAL DAN COVID 19 - Muhlis, Muhlis (Jurnal Ar-Ribh, 2020)
Respond to the current situation, , financial institutions Islamic non-bank are developing technology-based service provision in order to maintain the company's stability in the current millennial era, people who tend to use technology. The purpose of this study was to determine the importance of implementing risk management strategies in service development through information technology in non-Islamic banking financial institutions. The methodology used is through a research library study. The results show that risk management strategies in the development of digital technology services are needed to fence and protect users and non-Islamic bank financial institutions, because the current risks are so complex, both financial and non-financial in the era of disruption and the state of the Covid 19 virus outbreak with users millennial society.